Quality assessment of maize tortillas produced from landraces and high yield hybrids and varieties - Acosta-Estrada, Beatriz A.; Serna-Saldívar, Sergio O.; Chuck-Hernández, Cristina (Frontiers in Nutrition, 2023)
Introduction Different analyses of the profiles of tortillas have been made using the traditional method, whether from landraces or hybrids versus those made with dry masa flour in which significant variability (p < 0.05) is reported in favor or against each type of tortilla which may be due to various factors such as the type of maize or the processing methods. Methods Twenty-two samples including hybrids, hybrid mixtures, varieties, landraces and dry masa flours were processed to masa and tortilla under similar and controlled conditions and tortilla quality evaluated. In total, 70 characteristics were analyzed as physicochemical properties of the maize (e.g., hectoliter weight and dimensions), processability characteristics, masa characteristics [e.g. viscoamylographic parameters (RVA)], and quality parameters of tortillas (e.g., sensory performance, color and texture). Results and discussión The studied materials presented variability among genotypes, especially within landraces. The physical and chemical properties of corn affected the processability and quality characteristics of tortillas (sensory and composition), and it was found that high producing hybrids and varieties (p < 0.05) were better and more consistent in all stages of processing. Forty percent of the landraces yielded masa with poor machinability. Conclusion Landraces averaged 1.27 percentage points more protein (p < 0.05) than other analyzed samples and they comparatively yielded tortillas with lower extensibility (12.34%) compared to counterparts produced from hybrids and varieties. This work provides valuable information on how the chemical and physical characteristics of different types of maize genotypes affect the nixtamalization process and the quality of tortillas to provide more elements in the selection of the most appropriate genotypes for tortilla production.